Low platelet count is potentially the most important contributor to severe bleeding in patients newly diagnosed with acute promyelocytic leukemia - Song Y (OncoTargets and Therapy, 2017)
Yu-hua Song,1,2 Peng Peng,3 Chun Qiao,1 Run Zhang,1 Jian-yong Li,1 Hua Lu1 1Department of Hematology, The First Affiliated Hospital of Nanjing Medical University, Jiangsu Province Hospital, 2Department of Hematology, 3Department of Oncology, The Second Hospital of Nanjing, Nanjing, People’s Republic of China Abstract: The objective of the current study was to provide more appropriate therapeutic strategies for reducing severe hemorrhaging by assessing the recovery of abnormal coagulation indexes in patients with acute promyelocytic leukemia (APL) during induction therapy. Retrospective analyses of 112 patients newly diagnosed with APL were performed during initial treatment. In our study, the early death rate was 5.36%. Hemorrhage was the leading cause of death during the induction period (4/6). The values of white blood cell count, lactate dehydrogenase, prothrombin time (PT), fibrinogen (Fbg), hemoglobin, and bone marrow leukemic promyelocytes were significantly different in the high-risk group compared to the low/intermediate-risk groups. There were significant differences in the white blood cell count, bone marrow leukemic promyelocytes, platelet (PLT) count, and the levels of lactate dehydrogenase, d-dimer, PT, and Fbg, as well as in FLT3-ITD mutations between patients with major bleeding and those with minor bleeding. Hemostatic variables significantly improved over time during induction therapy. The recovery times of the PLT, PT, and Fbg values were significantly slower in patients with major bleeding than in those with minor bleeding. Specifically, the PLT level in patients with major bleeding was not similar to that in the minor bleeding group until after 4 weeks of treatment. Hemorrhages were the most common cause of induction death in this study. High-risk patients were more prone to serious clinical bleeding symptoms. Patients with major bleeding had more rapid proliferation characteristics and an increased incidence of FLT3-ITD mutations compared to patients with minor bleeding. Hemostatic variables recovered significantly more slowly in patients with major bleeding than in those with minor bleeding. Active induction therapy and blood product infusion are effective in preventing severe bleeding. Our results suggested that low PLT count might be the leading cause of fatal bleeding in patients newly diagnosed with APL. Keywords: acute promyelocytic leukemia, all-trans retinoic acid, arsenic trioxide, coagulation, hemorrhage